The Intellectual Structure of Early Childhood Education Research: A Bibliometric Study Based on Scopus Database - Nurhabibah Nurhabibah; Riska Ida Irawan; Muh. Thahirul Hakim; Ummu Fajariyah Akbari; Uslan Uslan (Eastasouth Institute, 2026)
This study aims to map the intellectual structure of early childhood education research through a bibliometric analysis of publications indexed in the Scopus. The data were collected using relevant keywords such as “early childhood education,” “preschool education,” and “early learning,” within a specified time frame. The bibliographic data were analyzed using VOSviewer to examine co-authorship networks, keyword co-occurrence patterns, citation structures, and the temporal evolution of research themes. The results reveal that early childhood education research is characterized by three major interconnected clusters: educational practices, child development and health, and epidemiological or longitudinal studies. The findings also indicate a clear shift in research focus over time, from health-oriented and developmental perspectives toward more education-centered themes such as teaching, preschool systems, and early learning environments. Density analysis further highlights core research areas alongside emerging topics, including mental health and gender, which remain relatively underexplored. This study contributes to the literature by providing a comprehensive and systematic overview of the knowledge structure and development of early childhood education research, offering valuable insights for researchers, educators, and policymakers in identifying research gaps and future directions.